Peran Pemicu dan Kondisi sebagai Moderasi Pengaruh Kepuasan terhadap WOM (Studi pada Restoran/Rumah Makan di Surabaya) - Setyawati, Endang; Hadiwidjojo, Djumilah; setiawan, Margono; .., Solimun (Universitas Brawijaya, Indonesia, 2012)
Theoretically, it is assumed that service quality affects consumer satisfaction. If the consumer is satisfied with the service, the consumer is likely to be willing to give positive recommendation to other consumer. Nowadays, restaurants faces so many challenges to retain their customers and to prevent them from turning to the other restaurants. The shifting of consumers to other restaurants may be due to dissatisfaction to the service given by one restaurant. Therefore, one solution to this problem is increasing the quality of service. However, to only improve the quality of the service is not enough to attract customers because there are other factors triggering the consumers to give positive recommendation to other consumers. That factor is Word of Mouth (WOM). The objective of this research is to find out the effect of service quality (technical and functional) on WOM. The research also examines the role of the triggering variable and the condition variable as the moderator between satisfaction and WOM. This research is conducted on the restaurant consumers in Surabaya. The sampling technique used is non-probability sampling, that is accidental sampling. The data were obtained from 150 restaurant customers, who are analyzed using PLS. The results of analysis indicate that the quality, type, and variation of food and beverages provided, as well as prime service given by restaurants, all influence consumer satisfaction. The satisfied consumer about the service given will impact their willingness to give good word and positive recommendation to other consumers. The consumers may give more intensive and positive recommendation if there are surprise, discounts or special coupon given to them.